A Novel PDK1/MEK Dual Inhibitor Induces Cytoprotective Autophagy via the PDK1/Akt Signaling Pathway in Non-Small Cell Lung Cancer - Rangru Liu; Zhuo Chen; Gaoyun Hu; Zutao Yu; Qianbin Li; Danqi Liu; Ling Li; Zhaoqian Liu (MDPI AG, 2023)
In a preliminary study, we synthesized a series of new PDK1/MEK dual inhibitors. Antitumor activity screening showed that Compound YZT exerts a strong inhibitory action in A549 cells. However, the specific mechanism of YZT against non-small cell lung cancer (NSCLC) is largely unknown. This work confirmed the anti-proliferation and pro-apoptosis effects of YZT in NSCLC cells. Furthermore, YZT promotes autophagy and provokes complete autophagic flux in NSCLC cells. Notably, compared with YZT alone, the combination of YZT with the autophagy inhibitor chloroquine (CQ) or 3-methyladenine (3-MA) markedly strengthened the anti-proliferative and pro-apoptotic actions, suggesting that YZT-induced autophagy is cytoprotective. We further found that YZT-induced autophagy may exert a cytoprotective function by preserving the integrity of mitochondria and decreasing mitochondrial apoptosis. Moreover, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis suggested that PDK1 is an upstream protein of the Akt/mTOR axis and western blotting verified that YZT induces autophagy by the PDK1/Akt/mTOR signaling axis. Finally, YZT plus CQ significantly enhanced the anticancer activities compared to YZT alone in an animal study and immunohistochemistry showed that the level of LC3 was increased by YZT, which is in line with the in vitro results. In short, our study provides reliable experimental basis for developing Compound YZT as a new chemotherapeutic drug candidate and suggests that combined administration of YZT with CQ is a potential therapy against NSCLC.